Pathophysiological Relationships between Cardiovascular Hyperreactivity, Obesity and Sedentary Lifestyle - Milagros Lisset León Regal; Lázaro Hermes González Otero; Annerys Morffi Crespo; Angélica Figueredo López; Elianet Ramírez Porras; Liannet Fernández de Paz (Revista Finlay, 2022)
It is necessary to continue arguing the pathophysiological relationships between a sedentary lifestyle, cardiovascular hyperreactivity and obesity as risk factors for cardiovascular diseases, which are interdependent and whose prevalence currently remains high. The objective of this study was to argue the pathophysiological relationships between cardiovascular hyperreactivity, obesity and sedentary lifestyle. For this, a total of 24 bibliographic references were consulted between primary and secondary sources, as well as other sources of information that were accessed through the main managers. Risk factors for cardiovascular diseases are additive. Sedentary lifestyle and obesity are factors closely related to each other; in turn they are associated with increased activity of the sympathetic axis, with the onset of cardiovascular hyperreactivity as a phenomenon that increases the risk of suffering from high blood pressure and other cardiovascular diseases.